A Critical Exploration of Human-Primate Dynamics and Ecological Reflections in ‘Rise of the Planets of the Apes’ Movie: An Ecocriticism Literary Analysis - Zulkarnaen, Dicky Morgana; Saraun, Mychelle Ayde Abigail; Clara, Scarlet; Chendra, Rivalio; Pane, Charrine Sefanya Fiorentina Fiorentina (Jurnal Pendidikan Makarios, 2023)
This journal article offers an ecocritical analysis of the film "Rise of the Planet of the Apes" through the lens of Hiltner's "Ecocriticism" (2014). Employing a qualitative methodology, the study examines the movie's portrayal of human-animal relationships and environmental ethics. Additionally, the article delves into the cinematography of the film, focusing on the use of camera techniques to convey environmental and ethical themes. As the result: 1) The interconnectedness among humans, apes and environment portrays ethical concerns regarding the separation of apes with their habitat for medical experiment. 2) The human-animal relationships depicted shows that the apes' yearning for freedom and acceptance creates ethical implications: being seen as part of a family and as a mere experimental subject. 3) The disruption of ecosystems by human actions, particularly the apes' habitat, exploitation and abuses has made severe disruption both the humans and the apes, caused by the injustice experienced by the apes. This aligns with the film's broader portrayal, highlighting the interconnectedness between human exploitation, environmental disruption, and the need for ethical considerations.